Rancang Bangun Sistem Pendingin Sekunder Untuk Kabin Mobil Dengan Memanfaatkan Thermoelektrik (TEC) - Ramadhan, Faishal (Institut Teknologi Indonesia, 2019)
The air conditioner (AC) system of the car will stop when the car's engine is turned off, this causes the temperature in the cabin of the car to increase. The increase in temperature is caused by the cabin being closed so that there is no air circulation and also influenced by the temperature of the environment. Designing, assembling and testing the cooling system using peltier, fan, heatsink and pump as the main component. The test was carried out for 1 hour 30 minutes, with variations in the number of peltier working 2, 4 and 6. The results obtained were 2 peltier 28oC, 4 peltier 27.5oC and 6 peltier 27.5oC. The same results at 4 and 6 peltier where at 6 peltier there is a temperature increase then a decrease occurs. This is because the voltage received by peltier is not stable. The best results are obtained by the number of peltier 4 pieces, because the voltage received is stable so the temperature drops constantly.Â Â Â